Modeling of Shot Noise in Resonant Tunneling Structures. Issue 1 (1998) - Iannaccone, G.; Macucci, M.; Pellegrini, B.
Abstract : In this paper, we present insights into the transport properties and the geometrical structure of resonant tunneling devices that can be obtained by the study of their noise properties. We stress the importance of including noise behavior among the objectives of device simulations. The reason is twofold: on one hand, as the number of carriers involved in device operation decreases, fluctuations become more relevant; on the other hand, in devices whose functionality is based on quantum effects, noise properties strongly depend on the details of device geometry.